Community Practice Textbook Is Oriented Toward Graduate Study - David J. Edelman (The University of Alabama, 2022)
Review of the book: Dorothy N. Gamble and Marie Weil, Community Practice Skills: Local to Global Perspectives, New York: Columbia University Press, 2010. 482 pages. ISBN 978-0-231-11002-0